COMMUNITY PERCEPTION OF CHANGES IN LIVELIHOOD ASSETS IN THE RELOCATION AREA AT JATINEGARA BARAT FLATS - Rohman, Fatchur; Astuti, Winny; Rahayu, Paramita (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Settlement relocation is a program initiated by the Provincial Government of DKI Jakarta aimed at providing decent housing for the community. Kampung Melayu Village was one of the locations where relocation to the Jatinegara Barat Flats was implemented in 2015. Settlement relocation has varied impacts due to differing community perceptions. Therefore, this study aims to determine the community’s perception of changes in livelihood assets resulting from the relocation of settlements along the Ciliwung River, focusing on human capital, social capital, physical capital, environmental capital, and financial capital. The method used was scoring analysis and descriptive quantitative approaches, utilizing questionnaires and open interviews with the Jatinegara Barat Flats community affected by the relocation. The results of this study indicate that the relocated residents of Jatinegara Barat Flats experienced positive changes in their livelihood assets, with an overall score of 70.99%.